Self-reported worry and action among Vietnamese citizens during the COVID-19 pandemic in 2021: latent class analysis - Pham Quoc, Hung; Dao Anh, Son; Pham Anh, Tung (Intelektual Pustaka Media Utama, 2024)
Describe the prevalence of and factors associated with self-reported worry and actions of Vietnamese citizens during the COVID-19 pandemic in 2021. A secondary data analysis was implemented using a cross-sectional survey conducted in 2021 among 447 adults living in Hanoi City from July to December 2021 and Ho Chi Minh City from May to October 2021. The hidden layers assessment results retained the 3-class model as the best-fitting one in the study. In this model, 28.4% of participants were in Class 2 -